Dawson type polyoxometalate based-poly ionic liquid supported on different carbon materials for high-efficiency oxidative desulfurization with molecular oxygen as the oxidant. (18th November 2020) - Gao, Yan; Lv, Ziyan; Gao, Ruimin; Hu, Guangfa; Zhao, Jianshe
Abstract : A kind of supported catalyst was facile synthesized with polyoxometalate based-poly (ionic liquid) as active components and different carbon materials as supporter. The supported catalyst P[C2 VP]MoV/AC possesses high activity for 99.4% DBT removal rate. Abstract : Due to the increasingly severe environmental pollution, there is an urgent need to find a new catalyst with high efficiency and stability for deep desulfurization of fuels. In this work, hybrid material based on vanadium-substituted Dawson type polyoxometalate and poly ionic liquid was facilely prepared and successfully loaded on different carbon materials to produce a supported catalyst for oxidative desulfurization. The test result shows that the catalyst P[C2 VP]MoV/AC possesses high activity with the DBT conversion of 99.2%. At the same time, the catalyst with large specific surface area has more opportunities to react with sulfides and thus possesses high activity. According to the kinetic study, it is confirmed that the oxidation reaction of DBT follows first-order kinetics.